Low failure recovery cost controller placement strategy in software defined networks - Qi WU; Hongchang CHEN (网络与信息安全学报)
The controller placement is an important problem in software defined networks.Existing researches pay more attention to deploying controller planning for node failures and ignore the fact that the link failure can also effect the network drastically.To solve the problem,a mathematical model for the controller placement that plans ahead for the link failures to avoid a drastic increase failure recovery cost was proposed.To solve the model,an algorithm based on simulated annealing was designed.The simulation results show that the proposed model and algorithm can improve the robustness of the network.The maximum failure recovery cost is significantly reduced when a link falls in failures.